Facebook addiction among medical students: prevalence and consequences - Eman Fouad Mohamed; Amany Elshabrawy Mohamed; Amira Mohamed Youssef; Mohammad Gamal Sehlo; Eman Seif Alnasr Soliman; Abdallah Saad Ibrahim (Middle East Current Psychiatry)
Abstract Background Social media addiction, mainly Facebook, is a common emerging behavior, particularly among teens and young adults. The current study’s primary goal is to determine the prevalence of Facebook addiction and assess its influence on academic performance and mental health among medical students. Methods Six-hundred twenty-seven students from the Faculty of Medicine, Zagazig University, at Egypt were included at this cross-sectional study. A semi-structured questionnaire designed by authors was used to collect sociodemographic data and data about academic performance and sleep. Facebook addiction was investigated using a scale which is Bergen Facebook Addiction Scale (BFAS). The Depression Anxiety Stress Scale-21 (DASS-21) was utilized to screen for anxiety, depression, and stress. Results Between medical students, 16.6% had score above 24 and considered to have Facebook addiction. Facebook addiction had a substantial association with uncontrollable Internet use, affection of study hours, and decrease in academic scores. There is statistically considerable relation between Facebook addiction and anxiety, depression, and stress. Conclusions Facebook addiction is common among medical students and had a negatory impact on both their academic achievement and mental health.